Antidepressant and antinociceptive activities in animal models and in vitro assessment of the anti-thyroid activity of bis(DL-pyroglutamate)magnesium complex - Martini, Nancy (2019)
Background: Magnesium is an essential element related with biochemistry of the brain and different types of depression have been associated with its deficiency. Methods: The structure of a novel magnesium bis(DL-pyroglutamate) (Mg(DL-pGlu)₂) was elucidated by X-ray crystallography. Wistar rats were used in the in vivo experiments. The antidepressant-like effect was assessed by the forced swim test (FST) and the antinociceptive activity was evaluated using hot plate test. In both, non-specific effects were evaluated by the open field test. Anti-thyroid activity was examined using Lang’s method. Albumin binding behavior was evaluated by 3D fluorescence spectroscopy. Results: For the Mg(DL-pGlu)₂ complex (30 mg/kg), the FST test on Wistar rats revealed a decrease of 22% in the immobility time and an increment of 106% in the swimming time. The compound alters neither the locomotor activity nor the body weight after chronic administration. At the same dose, it showed antinociceptive activity, increasing the response latency. It blocks iodination reactions generating a charge transfer complex with iodine hence indicating anti-thyroid activity (Kc = 45366.5 ± 29 M⁻¹). Albumin 3D fluorescence spectroscopy experiments showed intensity increase of peak A and decrease of peak B. Conclusions: The results showed that the new compound produced a lowering of the immobility time and an increment of the swimming ability of the rats. The compound is able to increase the response latency in 70.0%, to capture iodine (anti-thyroid activity) and to interact with albumin through covalent type of interaction of the free NH groups.